Turkish Cypriot Economy, March 2021 : Impact of the COVID-19 Pandemic – A Path to Building Back Better - World Bank Group (World Bank, Washington, DC, 2021)
The special topic of this edition of the Macroeconomic Monitoring report focuses on the TC administration’s ‘public’ financial support to the agriculture sector. Due to the Turkish lira depreciation, the recent adverse climate conditions, and exacerbated by the COVID-19 crisis, the agriculture sector suffered significantly in 2020. However, the severe impact on the sector was also the result of several long-standing inefficiencies and low productivity. Financial support from the central budget for agriculture comes at a significant fiscal cost to the overall TC economy, while at the same time agricultural productivity has been stagnating. The COVID-19 pandemic has served to exacerbate these existing challenges through disruptions along the food value chain. These problems have affected small-sized farmers the most, given that they are the most vulnerable to income shocks and higher retail prices. Reforming the subsidy system for agriculture could help generate greater fiscal space in the medium term, and also help foster economic diversification and enhance productivity.